Beta-haemolytic streptococcal endocarditis: clinical presentation, management and outcomes. Issue 5 (3rd May 2016) - El Rafei, Abdelghani; DeSimone, Daniel C.; DeSimone, Christopher V.; Lahr, Brian D.; Steckelberg, James M.; Sohail, Muhammad R.; Wilson, Walter R.; Baddour, Larry M.
Abstract: Background Beta-haemolytic streptococcal (BHS) endocarditis is rare, but well-recognised for its high morbidity and mortality. This study sought to further characterise clinical features, management and outcomes of BHS endocarditis.Methods Retrospective review of all adultpatients (≥ 18 years old) with BHS endocarditis treated at the Mayo Clinic from 1 January 2000 to 31 December 2014.Results Forty-nine cases of BHS endocarditis were identified with a mean (± SD) age of 64 (±14.9) years and 65% were males. The infection was community acquired in 92% of the cases, with a median (IQR) time to diagnosis from symptom onset of 6 days (5–10). Associated conditions included the presence of a prosthetic valve (41%), malignancy (33%) and diabetes mellitus (DM) (31%). Median (IQR) vegetation size was 12 mm (9–17 mm). In a univariate analysis patients with DM had larger vegetations, median (IQR) = 17 mm (10.5–26 mm) compared to non-diabetic patients, median (IQR) = 11 mm (8–15 mm) ( p  = 0.01). Septic brain emboli occurred in 43% of cases. Eighteen patients (37%) underwent early (within 30 days) surgery. All-cause 1 month and 6 month mortality rates were 25% and 31%, respectively.Conclusion BHS endocarditis has an acute onset and is complicated by relatively large vegetations with a high rate of systemic embolisation. DM was the second most common associated medical condition and patients with DM had larger vegetations. Despite medical and surgical advances, mortality due to BHS endocarditis remains high, particularly within 30 days of diagnosis.